ANALISIS KANDUNGAN ZAT BESI DAN UJI ORGANOLEPTIK COOKIES DAUN BAYAM MERAH DENGAN SUBSTITUSI TEPUNG KACANG HIJAU - Alwiyah Ibrahim, Siti; Kadir, Sunarto; Septian Maksum, Tri (Jurnal Ilmu Psikologi dan Kesehatan (SIKONTAN), 2026)
Cookies are a type of baked treat popular among teenagers, characterized by a soft dough, a crisp texture, and a fat content that makes them a potential option for preventing and managing anemia. To enhance their nutritional value, recipe modifications involving iron-rich ingredients—such as red spinach leaves and mung bean flour—are necessary. The research problem addressed the iron content and consumer acceptance (via organoleptic testing) of red spinach cookies substituted with mung bean flour. This study aimed to analyze the iron content and conduct organoleptic testing on these cookies. It employed a pre-experimental design (specifically a one-shot case study) utilizing UV-Visible spectrophotometry and organoleptic testing. The study involved 20 semi-trained panelists recruited from students specializing in Nutrition within the Public Health Department at Universitas Negeri Gorontalo. Data were analyzed descriptively and presented in frequency distribution tables. The results indicated iron contents of 150 mg/kg, 100 mg/kg, and 124 mg/kg for the 5g, 10g, and 15g substitution formulations, respectively. Organoleptic test results showed that each formulation excelled in different parameters. The best formulation was the 5g variant (P1), with panelist acceptance rates of 70% for color, 80% for aroma, 85% for texture, and 90% for taste. Further research is recommended regarding other nutritional components, the use of different baking methods, and the shelf life of the cookies.